Fiber-based mode converter for generating optical vortex beams - Chen Ruishan (Institue of Optics and Electronics, Chinese Academy of Sciences, 2018)
In this work, an all-fiber-based mode converter for generating orbital angular momentum (OAM) beams is proposed and numerically investigated. Its structure is constructed by cascading a mode selective coupler (MSC) and an inner elliptical cladding fiber (IECF). OAM modes refer to a combination of two orthogonal LPlm modes with a phase difference of ±π/2. By adjusting the parameters and controlling the splicing angle of MSC and IECF appropriately, higher-order OAM modes with topological charges of l = ±1, ±2, ±3 can be obtained with the injection of the fundamental mode LP01, resulting in a mode-conversion efficiency of almost 100%. This achievement may pave the way towards the realization of a compact, all-fiber, and high-efficiency device for increasing the transmission capacity and spectral efficiency in optical communication systems with OAM mode multiplexing.